Use of different types of fibers to improve the mechanical properties of asphalt: A literary review - Adrianzen Flores, Orlando Jefferson (2025)
The demand for the use of flexible pavements is growing rapidly due to its good performance, but this is being affected considerably due to increased traffic and climatic variations, this brings with it the presence of considerable failures in the pavement, causing its performance to decrease and, therefore, its useful lifetime is shortened. This document aims to carry out a systematic review of the different types of fibers used in asphalt mixtures to improve their mechanical properties, in addition to studying the optimal percentages and lengths, the tests used, the performance of the mixtures according to the type of bitumen, the type of asphalt mix, and finally the profitability provided by the use of fibers in asphalt mixes is reviewed. Eighty-one articles published between 2014 and 2021 in the Scopus and Ebsco databases were reviewed. The reviewed papers had the same objective of studying the mechanical characteristics of asphalt mixtures using fibers. It was concluded that the fibers improve the properties of flexible pavements and, in addition, are profitably good despite having an increase in the initial cost, they demonstrate an increase in the life cycle, thus being economically feasible for road projects that are carried out with the use flexible pavements. It is also recommended to continue with studies aimed at using this type of asphalt mixture.